Students’ Perspectives on the Writing Supervisory Feedback in Indonesian and Malaysian Academia - Sujarwati, Iis; Othman, Juliana; Harahap, Alamsyah; Yueh Yea, Lo (Tarbawi : Jurnal Ilmu Pendidikan, 2024)
The study investigated the crucial role of supervisory feedback in academic supervision from students' perspectives in two distinct English-speaking university contexts: EFL and ESL. The research included the participation of 59 students and relied on a comprehensive methodology, utilizing a combination of questionnaires and semi-structured interviews for data collection. In analyzing the data, the study employed simple statistics to measure frequency and mean, while interview data were subjected to thematic analysis. The study's findings revealed that students in both Indonesian and Malaysian university contexts reported similar experiences concerning supervisory feedback. Specifically, their supervisors were found to provide comprehensive feedback and consistently engage in regular face-to-face meetings. However, the study identified a notable disparity in the preferred types of supervisory feedback between Indonesian and Malaysian students. Indonesian students preferred oral feedback, while Malaysian students leaned towards written feedback. These findings have important implications for academic supervision in Indonesian and Malaysian contexts. By shedding light on the differences in student feedback preferences, the study aims to increase awareness and provoke discussions about how supervisory feedback is administered. This, in turn, could potentially lead to positive changes in how academic supervision is conducted in these contexts. Ultimately, by exploring students’ perceptions of supervisory feedback, the study functions as a valuable resource that can inform the refinement of current feedback approaches to better align with the needs of students, thus enhancing the quality of academic supervision and the overall educational experience.